ETHICAL CONSIDERATION IN CONCEPTION OF INFECTIOUS DISEASES ERADICATION - O. I. Kubar; M. A. Bichurina; N. I. Romanenkova; N. I. Rosaeva; N. V. Zheleznova; I. N. Lavrentieva; A. Yu. Antipova; O. I. Kanaeva (Инфекция и иммунитет, 2018)
.